2019
DOI: 10.1101/728899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Notch signaling coordinates ommatidial rotation in the Drosophila eye via transcriptional regulation of the EGF-Receptor ligand Argos

Abstract: In all metazoans, a small number of evolutionarily conserved signaling pathways are reiteratively used during development to orchestrate critical patterning and morphogenetic processes. Among these, Notch (N) signaling is essential for most aspects of tissue patterning where it mediates the communication between adjacent cells to control cell fate specification. In Drosophila, Notch signaling is required for several features of eye development, including the R3/R4 cell fate choice and R7 specification. Here we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 85 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…We have previously reported that Notch signaling in R3/R4 pairs is critical to coordinate OR via Notch-signaling feeding into its transcriptional regulatory mechanism(s) (Koca et al, 2019). Our studies suggested that Notch signaling in R4 directly promotes the transcription of aos, encoding an inhibitory ligand to EGFR, and thus fine-tunes the critical EGFR signaling activity (Gaengel and Mlodzik, 2003) within the OR process (Koca et al, 2019).…”
Section: Multiple Notch Regulated Inputs Into the Or Processmentioning
confidence: 82%
See 3 more Smart Citations
“…We have previously reported that Notch signaling in R3/R4 pairs is critical to coordinate OR via Notch-signaling feeding into its transcriptional regulatory mechanism(s) (Koca et al, 2019). Our studies suggested that Notch signaling in R4 directly promotes the transcription of aos, encoding an inhibitory ligand to EGFR, and thus fine-tunes the critical EGFR signaling activity (Gaengel and Mlodzik, 2003) within the OR process (Koca et al, 2019).…”
Section: Multiple Notch Regulated Inputs Into the Or Processmentioning
confidence: 82%
“…To understand whether the contrasting apical localization pattern of dAbl between R3/R4 is important for OR, we aimed to perturb dAbl function and localization specifically in cells of the R3/R4 pair. To this end, we employed the md0.5-Gal4 driver which is initially active in both R3/R4 precursors and later becomes specifically upregulated in R4 as a result of Notch-mediated R4 specification (Cooper and Bray, 1999;Koca et al, 2019). md0.5-Gal4 mediated knockdown (KD) of dAbl, within R3/R4 pairs led to a significant aberration in the rotation pattern of ommatidial clusters as compared to wild-type, with clusters generally rotating faster (Figure 4A-B,D; Suppl.…”
Section: Abl Kinase Is Apically Enriched and Required In R4 To Slow Down Ormentioning
confidence: 99%
See 2 more Smart Citations
“…These include signalling by the small GTPases RhoA and Rac, upstream of Rho kinase [36,4345] and modulation of E-cadherin and N-cadherin expression via the kinase Nemo [4649]. Notch activity in the R4 cell also contributes to rotation by regulating EGF signalling [46,5053].…”
Section: The Core Planar Polarity Pathway In Drosophilamentioning
confidence: 99%